(untitled) (INTERNATIONAL JOURNAL OF CONSTRUCTION ENGINEERING (IJCE), 2021)
In 2019, PT Adaro Indonesia carried out a program of installing aramco culverts with a diameter of 3 meters and construction of gabions at the inlet and outlet sections at Sta 70+200 HW, to replace the function of culvert construction at Sta 70+300 HW which was no longer functioning. well. However, the condition of the aramco culvert installation construction project and gabion construction, as of February 2, 2020, is still in the form of construction progress of 90.62%. Even though the planned target is to start on July 29, 2019 and finish on September 29, 2019. In this project, there are several factors that are thought to affect project delays. This research was conducted to find the real causes of the constraints on the project. This study used a questionnaire and interview instruments. Respondents were selected with the assumption that they had been involved in or worked on a sump and mud drainage installation project. The data is then tested and after being declared valid and reliable then analyzed using the FMEA (Failure Modes and Effects Analysis) method. The results showed that 3 items became the dominant project risk factors, namely the risk of project failure due to changes in planning and specifications (RPN 706.90), Project failure risk due to no project delay penalty (RPN 633.70), Project failure risk due to late delivery of materials to the site (RPN 436.67). Based on the foregoing, further observations and interviews were conducted to obtain mitigation recommendations as a strategy to minimize the potential risk of project failure. The proposed risk mitigation strategy is with careful planning with observations in accordance with actual field conditions, using a professional/competent third party (planning consultant) in planning and design, using the Procrument Road method in the form of Design and Build, a binding contract is enforced between the implementer and the contractor. owner, include in the contract documents related to the penalty scheme that must be accepted by the vendor if the project experiences delays or failures, applies more stock of stone material for gabion work and applies more than 1 river stone supplier selection.